KBG 206 MANUSCRIPT: R. NG. RANGGAWARSITA’S ROLE IN THE IDENTIFICATION OF BUDA SCRIPT - Jatmika, Nugraha Bektya (UI Scholars Hub, 2023)
This study aims to reveal the history behind the writing of KBG 206, both the development of the script, the author, and the purpose of its writing at the time the manuscript was written. The form of this research is descriptive qualitative research with the type of library research. This study presents the text edition according to the single-text editing method, namely the diplomatic edition. The theory used in reviewing the form of letters in KBG 206 is in accordance with the paleographic theory with analytic model of statics. The result of the analysis is known that the KBG 206 manuscript was written by R. Ng. Ranggawarsita with a writing form that tends to resemble the writing of the pujangga himself in 1840-1842. In addition, it is known that varied forms of buda script in KBG 206 show the comprehense of R. Ng. Ranggawarsita knowledge to buda script. The stamp found in the KBG 206 manuscript shows the importance of the text in supporting the interests of the Bataviaasch Genootschap. Sulukan ada-ada in the text of KBG 206 also illustrate the views and aspirations of R. Ng. Ranggawarsita to the culture at that time, in this case especially the buda script.